2015
DOI: 10.1016/j.jalz.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

MIND diet associated with reduced incidence of Alzheimer's disease

Abstract: Background In a previous study, higher concordance to the MIND diet, a hybrid Mediterranean-DASH diet, was associated with slower cognitive decline. In this study we related these three dietary patterns to incident Alzheimer’s disease. Methods We investigated the diet-AD relations in a prospective study of 923 participants, ages 58 to 98 years, followed on average 4.5 years. Diet was assessed by a semi-quantitative food frequency questionnaire. Results In adjusted proportional hazards models, the second (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
701
2
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 815 publications
(740 citation statements)
references
References 33 publications
20
701
2
17
Order By: Relevance
“…The “MIND-diet,” which incorporates elements of both the Mediterranean diet and the “DASH diet,” has been linked with a lower risk of cognitive impairment 91 and the development of AD. 92 It is recognized that association in epidemiological studies does not prove causality. The FINGER and PREDIMED-NAVARRA studies were controlled interventional studies, helping to confirm causality.…”
Section: Potential Benefits Of Early Diagnosis Of Cognitive Impairmentmentioning
confidence: 99%
“…The “MIND-diet,” which incorporates elements of both the Mediterranean diet and the “DASH diet,” has been linked with a lower risk of cognitive impairment 91 and the development of AD. 92 It is recognized that association in epidemiological studies does not prove causality. The FINGER and PREDIMED-NAVARRA studies were controlled interventional studies, helping to confirm causality.…”
Section: Potential Benefits Of Early Diagnosis Of Cognitive Impairmentmentioning
confidence: 99%
“…Certain diets show promising, preventive effects on brain aging and cognitive impairment in observational studies and in clinical trials [13]. Higher adherence to the Mediterranean diet (MeDi) is associated with a lower risk for AD [48]. Prospectively, we showed that a high percentage of daily calories derived from protein and fat were associated with a reduced risk of incident MCI, whereas a high percentage from carbohydrates was associated with an increased risk of incident MCI [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean diet [113], exercise [114] and caloric restriction [115,116] have been shown to modulate AD risk factors including the mitochondrial healthy homeostasis. In combination with these, several preventive approaches have been studied in AD patients, for example the antioxidant N-acetyl cysteine (NAC) [117], α-lipoic acid (LA) [118] and curcumin [119] have been tested.…”
Section: Therapeutic Approaches Targeted To Modulation Of Mitochondrimentioning
confidence: 99%